Phylogenetic Relationships of the Genus Homatula (Cypriniformes: Nemacheilidae), with Special Reference to the Biogeographic History around the Yunnan-Guizhou Plateau - Min, Rui; Chen, Xiao-Yong; Yang, Jun-Xing; Winterbottom, Richard; Mayden, Richard L. (Zootaxa, 2012)
Species of the nemacheilid genus Homatula are endemic to the Yunnan-Guizhou Plateau of China. Herein we provide phy-logenetic inferences of species relationships based on complete sequences of the mitochondrial cytochrome b gene (cyt b)and partial sequences of the nuclear recombination activation gene (RAG 1). Both gene trees (and the concatenated dataset) support the recognition of five clades in the genus. These analyses also support the hypothesis that two of the lineagesresolved represent undescribed species awaiting formal description, and, further, that two previously recognized speciesare junior synonyms; both are genetically indistinguishable from other previously recognized species. Divergence timesof the major clades in Homatula are inferred to be Late Pliocene and the Early Pleistocene, and are correlated with themassive geological events associated with the uplift of the Qinghai-Tibetan Plateau occurring at these times. The recon-struction of drainage histories suggests that the fish faunas of the Nu and Lancang rivers are basal relative to other riverinefaunas in the region, and that the Nanpan and the Jinsha rivers share a more recent history than with any other river systems included in our study.